Progress in the application of ultrasound in glioma surgery - Wu, Hao; Cheng, Yingying; Gao, Wenwen; Chen, Peng; Wei, Yao; Zhao, Haikang; Wang, Fenglu (Frontiers in Medicine, 2024)
Brain glioma, which is highly invasive and has a poor prognosis, is the most common primary intracranial tumor. Several studies have verified that the extent of resection is a considerable prognostic factor for achieving the best results in neurosurgical oncology. To obtain gross total resection (GTR), neurosurgery relies heavily on generating continuous, real-time, intraoperative glioma descriptions based on image guidance. Given the limitations of existing devices, it is imperative to develop a real-time image-guided resection technique to offer reliable functional and anatomical information during surgery. At present, the application of intraoperative ultrasound (IOUS) has been indicated to enhance resection rates and maximize brain function preservation. IOUS, which is promising due to its lower cost, minimal operational flow interruptions, and lack of radiation exposure, can enable real-time localization and precise tumor size and form descriptions while assisting in discriminating residual tumors and solving brain tissue shifts. Moreover, the application of new advancements in ultrasound technology, such as contrast-enhanced ultrasound (CEUS), three-dimensional ultrasound (3DUS), noninvasive ultrasound (NUS), and ultrasound elastography (UE), could assist in achieving GTR in glioma surgery. This article reviews the advantages and disadvantages of IOUS in glioma surgery.